Staged repair on a neglected paraphimosis in a 5-year-old-male - Barmadisatrio; N.Wisnu Sutarja; Illona Okvita Wiyogo (Elsevier, 2021)
Aims of the study: We report a rare case report of 5-year-old boy with a neglected paraphimosis for three days and a brief literature reviewed regarding paraphimosis. Case description: A 5-year-old male was brought to the hospital with a chief complaint of penile pain after failing to return the foreskin to its normal position for the past three days. Physical examination indicated normal vital signs. Local examination of the penis revealed a gross circumferential edema with a trapped prepuce, proximal to the penile glans. There weren't any signs of necrosis or urinary obstruction. Physical neurological examination revealed intact sensory function. A dorsal slit procedure was performed. Circumcision, as a follow-up procedure for cosmetic purposes, was performed five months afterwards. The long gap between the procedures was due to financial constraints. The patient displayed excellent clinical outcomes based on cosmetic appearance and urinary function, one month after he was discharged from the hospital. Conclusions: Staged repair consisting of dorsal slit and circumcision is possible in a neglected paraphimosis lasting three days with intact vascular and neurological functions.